Analysis of the transmission dynamics of COVID-19 in Minas Gerais: Modeling and Simulation (Research, Society and Development, 2020)
Understanding the spread and prevention of the new coronavirus (SARS-CoV-2) has become a challenge for infectologists, researchers and managers. This study aims to simulate and analyze the SEIR (Susceptible-Exposed-Infected-Recovered) mathematical model for COVID-19 transmission dynamics in Minas Gerais - Brazil. Additionally, the transmission was projected for 30 days, as well as the impact of different rates of social isolation on the flattening of the epidemiological curve. Scilab® software was used to implement a SEIR mathematical model. The parameters were adequate based on the real data provided by the State Health Secretariat (SES). The results showed that the model adequately represented confirmed cases (R2=0.994) and deaths (R2=0.991). The model  projection indicates that the peak of the disease in the state of Minas Gerais will occur around 08/20/2020. The scenario without social isolation estimates 10,060 deaths until 12/04/2020. The model projects a reduction of 987 victims with 50% isolation (9,073 deaths); 1,991 victims with 70% isolation (8,069 deaths) and 6,770 victims with lockdown (3,290 deaths). It can be said that the isolation measures are effective in flattening the COVID-19 contamination curve. Mathematical models can contribute to the choice of intervention strategies and reveal important aspects about disease spreads.